Implementation of Innovation-Based Corporate Social Responsibility Program at PT Pertamina Refinery Unit II Sei Pakning in Fostering the Entrepreneurial Spirit of Micro, Small, and Medium Enterprises - Seno Andri; Mandataris Mandataris; Ruzikna Ruzikna; Endang Sutrisna; Mashur Fadli (Budapest International Research and Critics University, 2022)
The purpose of this study is to see the extent to which implementation of innovation-based corporate social responsibility program at PT Pertamina Refinery Unit II Sei Pakning in fostering the entrepreneurial spirit of micro, small, and medium enterprises. This type of research uses a mixed method. The selection of informants is carried out using a purposive technique consisting of the Camat, Village Head, Manager of PT Pertamina Refinery Unit II Sei Pakning, Corporate Social Responsibility Team, Head of Farmer Groups and Community Actors of Micro, Small, and Medium Enterprises. Methods of data collection is done by means of observation, interviews, questionnaires and documentation. In quantitative data analysis technique is to use statistical analysis. The results show that product innovation, process innovation, method innovation, strategy innovation, and system innovation have a significant effect on entrepreneurial spirit. The suggestion from this research is that it is better for PT Pertamina Refinery Unit II Sei Pakning made improvements to the innovations of the corporate social responsibility program that they had carried out, especially in the innovation of the system that was carried out in order to continue to involve the district and village governments, so that there was support from both parties for the progress of the assisted the entrepreneurial spirit of micro, small, and medium enterprises.